Dificuldades de aprendizagem : uma discussão sobre as concepções de professoras - Soares, Ângela Mara Berlando (2012)
This work aims to analyze the conceptions present among teachers about learning disabilities and the influence that such beliefs have on learning processes. For this purpose, an exploratory study was performed through semi-structured interviews which data pointed the need to review the relationship among learning notions, deficiency, and learning disabilities. The exposition rebuilds the conceptions of deficiency throughout history, following the evolution path of learning disabilities up to current times. It also discusses the terminologies currently employed in diagnosis elaboration and completion of referrals to the process of evaluation or clinical psycho-pedagogical treatment, and the overlapping existent between these definitions regarding the underlying issues that it carries. It highlights the either inappropriate or deprived use of further theoretical terminologies for elaborating opinions and referrals to the clinical psycho-pedagogical assistance. The learning theme, under the psychopedagogy light and based on authors such as, Weiss (2003), Fernández (2001), Charlot (2000), Perrenoud (2001), Coll (2004), Pozo (2002), and Wood (2003), becomes compelling in the current context of education, and in the psycho-pedagogical clinic, where multiple facesare noted and analyzed in this research with the perspective to propose the resizing of conceptions, therefore, interfering in the pedagogical and psycho-pedagogical practice. The investigation here exposed intends to provide reflection on the existent conceptions regarding the learning process, and point out elements for (re) building a more meaningful and coherent reference to reality, which contemplates expectations and needs of individuals in this time